Embedding inertial-magnetic sensors in everyday objects: assessing spatial cognition in children - Campolo, Domenico (2013)
This paper describes an interdisciplinary approach to the assessment of children development of spatial cognition, with a focus on the technology. An instrumented toy (block-box) is presented which embeds magneto-inertial sensors for orientation tracking, specifically developed to assess the ability to insert objects into holes. The functional specifications are derived from experimental protocols devised by neuroscientists to assess spatial cognition skills in children. Technological choices are emphasized with respect to ecological requirements. Ad-hoc calibration procedures are presented which are suitable to unstructured environments. Preliminary results based on experimental trials carried out at a day-care on typically developing children (12-36 months old) show how the instrumented objects can be used effectively in a semi-automatic fashion (i.e., rater-independent) to derive accurate measurements such as orientation errors and insertion time which are relevant to the object insertion task. This study indicates that a technological approach to ecological assessment of spatial cognition in children is indeed feasible and maybe useful for identification and early assessment of developmental delay.